Simulations of high intensity laser-plasma interactions Generating radiation of extreme intensity - Mårtensson, Gustav (My University, 2015)
Abstract In this project the interaction between a dense plasma and a high-intensity laser pulse was studied through Particle-in-cell simulations. Nonlinear behavior in the plasma particle dynamics caused the ultra-relativistic particles to generate radiation of intensities much greater than that of the incident radiation. The possibility to boost laser intensities with a factor ∼ 103 could open up for the probing of nonlinear effects in vacuum. To explain the results a theoretical model called the Relativistic Electronic Spring Model was extended slightly to explain the behavior of the plasma particles during the interaction with the high-intensity laser of arbitrary polarization.
Keywords: Energi; Materialvetenskap; Grundläggande vetenskaper; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Fysik; Energy; Materials Science; Basic Sciences; Sustainable Development; Innovation & Entrepreneurship; Physical Sciences